Strategi Manajemen Mutu Pendidikan dalam Mewujudkan Peserta Didik Berkarakter dan Kompeten - Isroful Jannah; Ika Sofa Sofiana; Ahmad Royani; Nisa Islami (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2026)
Educational quality management strategies play a strategic role in shaping students who are both competent and possess strong character, in academic as well as non-academic aspects. The challenges of globalization and technological advancement require educational institutions to implement a well-planned, sustainable, and quality-oriented management system aimed at improving human resource excellence. This study aims to analyze educational quality management strategies in developing students with strong character and competencies that are relevant to the demands of the modern era. The research method employed is library research, by examining various literature sources such as books, scientific journals, educational policy regulations, and previous relevant studies on educational quality management. The data analysis technique is conducted through systematic data collection, classification, and interpretation in order to obtain a comprehensive understanding. The results of the study indicate that effective implementation of educational quality management includes quality planning, the execution of character-based programs, quality control, and continuous evaluation.The integration of character values into the curriculum, the improvement of teacher competencies, and the involvement of all stakeholders are key factors for success. Therefore, a structured and continuously improving educational quality management strategy can produce students who are not only academically excellent but also possess holistic character and competencies.